Nilai Gizi dan Serat Pangan pada Snack Bar Berbasis Tepung Kimpul (Xanthosoma sagittifolium) dan Kacang Gude (Cajanus cajan) - Nyoman Wahyu Meta Wulandari; Kadek Dyah Swasni Prambandita (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
The purpose of this research was to determine the effect of tannia flour and pigeon pea to produce the best snack bar with high dietary fiber and also with the good sensory. This research was an experimental study using a Completely Randomized Design (CRD) with a treatment ratio of tannia flour and pigeon pea were 70%:30%, 60%:40%, 50%:50%, 40%:60%, and 30%: 70%. Each treatment was repeated three times. The variables observed were moisture content, ash content, protein content, fat content, carbohydrate content, crude fiber content and sensory of snack bar (color, flavor, taste, texture). This best snack bar contains 5,31% water, 2,11% ash, 11,22% protein, 18,33% fat, 61,58% carbohydrate, 19,50% crude fiber. After getting the best snack bar with the effectiveness test, it was observed the levels of dietary fiber. Based on the results of the effectiveness test, the best treatment in this research was tannia flour and pigeon pea with ratio 30%:70%. This best snack bar contained 5.58% of fiber. The results of the sensory test of color were liking, while the flavor, taste, texture, and overall acceptance were like moderately. The results of the scoring test for color were brown, with a slightly distinctive tannia flavor, no itching taste, and a dense texture.